The bivalent ligand MCC22 potently attenuates hyperalgesia in a mouse model of cisplatin-evoked neuropathic pain without tolerance or reward. (1st November 2019) - Cataldo, Giuseppe; Erb, Samuel J.; Lunzer, Mary M.; Luong, Nhungoc; Akgün, Eyup; Portoghese, Philip S.; Olson, Julie K.; Simone, Donald A.
Abstract: Cisplatin and other widely employed platinum-based anticancer agents produce chemotherapy-induced peripheral neuropathy (CIPN) that often results in pain and hyperalgesia that are difficult to manage. We investigated the efficacy of a novel bivalent ligand, MCC22, for the treatment of pain arising from CIPN. MCC22 consists of mu opioid receptor (MOR) agonist and chemokine receptor 5 (CCR5) antagonist pharmacophores connected through a 22-atom spacer and was designed to target a putative MOR-CCR5 heteromer localized in pain processing areas. Mice received once daily intraperitoneal (i.p.) injections of cisplatin (1 mg/kg) for seven days and behavior testing began 7 days later. Cisplatin produced mechanical hyperalgesia that was decreased dose-dependently by MCC22 given by intrathecal (ED50 = 0.004 pmol) or i.p. (3.07 mg/kg) routes. The decrease in hyperalgesia was associated with decreased inflammatory response by microglia in the spinal cord. Unlike morphine, MCC22 given daily for nine days did not exhibit tolerance to its analgesic effect and its characteristic antihyperalgesic activity was fully retained in morphine-tolerant mice. Furthermore, MCC22 did not alter motor function and did not exhibit rewarding properties. Given the exceptional potency of MCC22 without tolerance or reward, MCC22 has the potential to vastly improve management of chronic pain due to CIPN. This article is part of the Special Issue entitled 'New Vistas in Opioid Pharmacology'. Highlights: Chemotherapy often causes peripheral neuropathy that can be chronic and painful. The bivalent ligand, MCC22, consists of a mµ opioid receptor agonist and a CCR5 receptor antagonist. MCC22 potently reduced chemotherapy-induced hyperalgesia produced by cisplatin in mice. MCC22 did not produce tolerance or reward.